Expression of a urokinase‐type plasminogen activator during tumor growth leads to angiogenesis via galanin activation in tumor‐bearing mice. Issue 11 (9th October 2017) - Yamamoto, Hiroyuki; Okada, Rina; Tanaka, Rika; Unno, Keiko; Iguchi, Kazuaki
Abstract : Small‐cell lung carcinoma releases progalanin. The released progalanin is activated via a nonclassical processing pathway, being processed into an active form of galanin (1–20) by plasmin in extracellular components. Plasmin is produced from plasminogen activators. To clarify the regulation of progalanin via plasminogen activation by urokinase and tissue‐plasminogen activator (t‐PA), we investigated the regulation mechanism for urokinase and t‐PA expression and their effect on galanin activation. Additionally, we studied the effect of activated galanin on angiogenesis. To determine the effect of cell density, we measured the expression levels of urokinase and t‐PA using real‐time PCR and plasminogen/gelatin zymography in a cell culture. The urokinase expression increased under both high cell density and presence of cell membrane fractions. However, urokinase increments induced by conditioned medium were low. These results indicate that expression of plasminogen activators is regulated by cell membrane factors. We used tumor‐bearing mice to clarify the expression of plasminogen activators and galanin activation. Real‐time PCR showed that urokinase was substantially higher in the central parts of tumors compared to the periphery, and this was confirmed by plasminogen/gelatin zymography. To evaluate the biological effect of plasminogen activators on tumor growth, we used tranexamic acid as a plasminogen inhibitor. Tranexamic acid decreased galanin (1–20) and the hemoglobin content of tumors and suppressed tumor growth. Additionally, galanin had no effect on the hemoglobin content of tumors derived from cells lacking GALR2. These results demonstrate the regulation of urokinase expression in tumors through progalanin activation in extracellular compartments, and confirm that galanin plays a role in angiogenesis. Abstract : In small‐cell lung carcinoma, some neuropeptides are expressed as a precursor and converted to an active form by plasmin. In this study, we demonstrated that cell membrane factors induce urokinase expression, which, in turn, activates plasminogen to plasmin. In addition, urokinase expression in tumors activated progalanin via plasminogen cleavage. Our results suggest that excessive tumor growth induces progalanin activation via the urokinase–plasminogen system.